2007
DOI: 10.1007/bf03175219
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methicillin-resistance (mec-A) gene inStaphylococcus aureus strains by PCR and determination of antibiotic susceptibility

Abstract: Methicillin-Resistant Staphylococcus aureus (MSRA) has become a frequent cause of serious infections. Extended hospitalization and antibiotic therapy have been identified as additional risk factors for MRSA carrier and infection. The aim of this study was to determine the incidence of MRSA infections in the hospitals affiliated to Hamedan University of Medical Sciences. Seventy S. aureus clinical strains were isolated from patients from June 2005 to June 2006 and examined by PCR and conventional microbiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Van Loo et al (2007) found 2 (2.53%) MRSA strains in 79 samples of raw pork and beef. In another research, Zamani et al (2007) showed that out of a total of 70, Staphylococcus aureus isolates obtained from the patients who consulted with the clinical centers of Hamedan Medical Science University and a private laboratory in Iran, 50% of the strains (35 cases) in PCR method, and 31.4% (22 cases) in antibiotic resistance patterns with disc agar diffusion method were resistant to methicillin. Nafisi et al (2008) researched on 52 isolates of coagulase positive S. aureus among 204 clinical staff workers of the different departments of Hajar Educational Institute, a subpart of Shahre Kord Medical Science University, using Agar Screen and Duplex PCR methods and reported that phenotypically 23 cases (44%) of the isolates, and genotypically (mecA) 27 cases of the isolates (52 %) are resistant to methicillin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Loo et al (2007) found 2 (2.53%) MRSA strains in 79 samples of raw pork and beef. In another research, Zamani et al (2007) showed that out of a total of 70, Staphylococcus aureus isolates obtained from the patients who consulted with the clinical centers of Hamedan Medical Science University and a private laboratory in Iran, 50% of the strains (35 cases) in PCR method, and 31.4% (22 cases) in antibiotic resistance patterns with disc agar diffusion method were resistant to methicillin. Nafisi et al (2008) researched on 52 isolates of coagulase positive S. aureus among 204 clinical staff workers of the different departments of Hajar Educational Institute, a subpart of Shahre Kord Medical Science University, using Agar Screen and Duplex PCR methods and reported that phenotypically 23 cases (44%) of the isolates, and genotypically (mecA) 27 cases of the isolates (52 %) are resistant to methicillin.…”
Section: Resultsmentioning
confidence: 99%
“…PCR product (5 μl) of each sample was mixed with 1 μl of sample buffer (6X: 0.25% bromophenol, 0.25% xylen cyanol, 15% ficol 400) and loaded on 1.5% agarose and electrophoresed in 75 volt for 60 min. The band of fragment was observed by ultraviolet (UV) transilluminator and was documented by gel analyser machine (Zamani et al, 2007).…”
Section: Pcr For Mec-a Gene Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential danger of the distribution of MRSA strains in a special care section has been paid attention due to the occurrence of more problems in the hospitals, various medical manipulation, and extensive consumption of antibiotics. Study of Zamani et al [18], on 70 samples of S. aureus, showed that 50% were MRSA and considering antibiotic-resistance pattern, they showed resistance to tetracycline (74.2%), co-trimoxazole (68.5%), erythromycin (68.5%), and ceftazidime (51.4%). Studies by Moradi et al [19], on 104 samples of S. aureus, showed that the highest rate of sensitivity was toward vancomycin (96.2%), chloramphenicol (88.2%), rifampin (81.7%), and the lowest rate of resistance was toward cefoxitin (40.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the rapid emergence of strains resistant to methicillin causes this antibiotic lost their effectiveness for their treatment. So epidemiological studies to understanding the prevalence of this Staphylococcus aureus strains seems necessary (Dinges et al, 2000;Deurenberg et al, 2005;Zamani et al, 2007;Sajith Khan et al, 2012). Methicillin-resistant strains of Staphylococcus aureus have mecA gene or MIC of 4 μg / ml or more (Hososaka et al, 2007).…”
Section: Discussionmentioning
confidence: 99%